P035 ETROLIZUMAB TREATMENT MODULATES SOLUBLE MADCAM-1 LEVELS IN SERUM IN PATIENTS WITH CROHN'S DISEASE. (7th February 2019) - Sandborn, William J; Panes, Julian; Fuh, Franklin; Erickson, Rich; Jacob, Rhian; Zhang, Wenhui; Tang, Meina T; McBride, Jacqueline
Abstract: Introduction: Etrolizumab, a monoclonal antibody to the β7 integrin, inhibits both α4β7:mucosal addressin cell adhesion molecule 1 (MAdCAM-1)–mediated lymphocyte trafficking to the gut mucosa and αEβ7:E-cadherin–mediated lymphocyte retention. In patients with ulcerative colitis (UC) from the Phase 2 EUCALYPTUS trial (NCT01336465), treatment with etrolizumab resulted in a reduction in serum levels of soluble (s) MAdCAM-1 compared with placebo; this reduction in sMAdCAM-1 paralleled a reduction in free β7 receptors in the peripheral blood, with complete receptor occupancy (RO) observed at day 5 after the first dose in both dose cohorts (100 mg and 300 mg). 1, 2 Pharmacodynamic (PD) activity in patients with Crohn's disease has yet to be evaluated. Aims & Methods: The effect of etrolizumab treatment on serum levels of sMAdCAM-1 (PD biomarker) and β7 RO in patients with moderate to severe Crohn's disease was evaluated in a substudy of cohort 1 of the Phase 3 BERGAMOT trial (NCT02394028). Patients were randomly assigned (2:2:1) to receive subcutaneously administered etrolizumab 105 mg once every 4 weeks, etrolizumab 210 mg at weeks 0, 2, 4, 8, and 12 or placebo during a 14-week induction period. Biomarker and pharmacokinetic (PK)/PD analysis was conducted using serum and whole blood samples obtained at baseline and weeks 1 (days 3, 4, or 5), 2, 4, 10, and 14 from patients who enrolled in the PK/PD substudy. Measurements of serum sMAdCAM-1 were performed using a validated assay on the Gyrolab xP immunoassay platform. Whole blood samples were evaluated by flow cytometry within 24-48 hours of collection to assess β7 occupancy and enumeration of peripheral blood lymphocyte subsets. Results: This preliminary analysis included 64 patients with Crohn's disease (etrolizumab 105 mg, n = 29; etrolizumab 210 mg, n = 24; placebo, n = 11). Patients treated with etrolizumab showed a decline in sMAdCAM-1 from baseline (week 1: group median decline of ~ 40%, weeks 4 through 14: group median decline of ~ 80%) with minimal (< 10%) changes from baseline observed in the placebo arm (Figure 1 ). β7 integrin receptors on "β7 high intestinal homing" CD3 + T cells were rapidly and completely occupied in etrolizumab-treated patients as indicated by a near 100% decrease in CD3 + T cells with "available" β7 receptors (Figure 2 ). Similar RO results were observed with CD4 + T, CD8 + T, and CD19 + B lymphocytes. There were no dose-related differences observed in sMAdCAM-1 reduction and RO. Conclusion: In this preliminary analysis, sMAdCAM-1 was reduced following etrolizumab treatment in patients with Crohn's disease. Full β7 RO was achieved with both doses of etrolizumab. Overall, results were similar to those reported in UC 1 and confirm the expected pharmacologic profile of etrolizumab. References: 1Fuh F et al. Presented at UEGW 2016. P0843. 2Vermeire S et al. Lancet. 2014;384(9940):309-318. Figure 1. Serum levels of sMAdCAM-1 (median/MAD) were greatly reduced following etrolizumab dosing. BL, baseline; MAD, median absolute deviation; sMAdCAM-1, soluble mucosal addressin cell adhesion molecule 1. Figure 2. Full β7 receptor occupancy (median/MAD) on intestinal homing CD3 + T cells was observed following etrolizumab dosing. BL, baseline; MAD, median absolute deviation.